(untitled) (Advancements in Homeopathic Research, 2022)
Renal stone is the most common urinary tract disease found worldwide. The prevalence of renal stone disease has increased considerably in the past few decades. Changes in lifestyle, faulty diet, too much psychological stress, and environmental factors are possible predisposing factors. Some patients may be asymptomatic or have atypical symptoms such as vague abdominal pain. In contrast, others will have more typical symptoms, such as acute abdominal or flank pain, nausea, urinary urgency, or frequency. The approach in conventional treatment gives no permanent solution. Homoeopathic constitution medicine treats the patient as a whole and seizes the recurrence. This article illustrates a case report of successful non-surgical expulsion of renal calculus by homoeopathic medicine to show the potentiality of homoeopathic medicines. 1,2